Development and evaluation of a rabies enzyme-linked immunosorbent assay (ELISA) targeting IgM and IgG in human sera - Zajac, Michelle Dawn (Kansas State University, 2019)
Rabies is nearly 100% fatal without the pre-or post-exposure prophylaxis vaccination series. Pre-exposure Prophylaxis (PrEP) vaccination series is administered to those persons in high risk occupations due to the evidence that PrEP is the most effective method of protection from a rabies infection. Rabies virus neutralizing antibody (RVNA) is required for the protection from rabies. However, the immune mechanism and antibody kinetics of isotype switching remains unclear by current diagnostic techniques. Knowledge of these kinetics will aid in making more informed decisions on the timing and number of vaccinations needed to elicit a sufficient antibody response for protection against exposure to rabies virus. Recently, the World Health Organization (WHO) supported alternative vaccine regimens that may affect peak levels of these subclasses of RVNA. Advisory Committee on Immunization Practices (ACIP) is also currently evaluating the rationale for ideal vaccine series for amending the current rabies prevention recommendations. To date, there has not been a rapid and reliable assay to detect and quantify antibody isotype switching from the primary antibody response of IgM to the subsequent IgG antibody response that occurs during the immune response to rabies vaccination. The principal requirement of this assay is that it can reliably and reproducibly determine and correlate responses to RVNA levels and monitor IgG versus IgM response, according to current guidelines. This knowledge will aid in the understanding of the immune response as a result of rabies virus infection or immunization using a currently approved vaccine and provide additional information to guide future research.
Keywords: Rabies; ELISA; Antibody; Immune response; Virology; Assay development